Processing technologies of IIVR for commercialization - Singh, Sudhir; Koley, T K; Singh, B. (Indian Horticulture, 2019)
Vegetables are important nutritional requirement of human beings for supplying vitamins, minerals and disease preventing phytochemicals. However, due to poor post-harvest management and processing facilities, a large quantity of vegetables perish, accounting to huge post-harvest losses. In India, valueaddition is confined to pickles, chutneys, preserves and candies, which is highly decentralized with unskilled labourers. Indian Institute of Vegetable Research, Varanasi, has standardized many low-cost processing technologies such as drying, steeping preservation, convenience leafy vegetables such as easy-to-cook leafy vegetables, vegetable based chips and instant bottle gourd kheer mix for commercialization.